2017
DOI: 10.1007/s40519-017-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin growth factor-1 correlates with higher bone mineral density and lower inflammation status in obese adult subjects

Abstract: In conclusion, our results show that higher levels of serum IGF-1 in obese patients correlate with lower inflammatory pattern and better skeletal health, as demonstrated by higher BMD and osteocalcin levels. These results lead to speculate the existence of a bone-adipose-muscle interplay modulating energy homeostasis, glucose, bone metabolism, and chronic inflammation in individuals affected by abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…In this regard, IGF-1 effects are produced by the enhancement of the function of mature osteoblasts ( 225 ) and promotion of osteoblast differentiation ( 226 ) and bone formation ( 227 229 ). Furthermore, higher levels of IGF-1 are associated with higher bone mineral density in adult obese individuals ( 230 ).…”
Section: Physiological Aspects Of Gh/igf-1 Axismentioning
confidence: 99%
“…In this regard, IGF-1 effects are produced by the enhancement of the function of mature osteoblasts ( 225 ) and promotion of osteoblast differentiation ( 226 ) and bone formation ( 227 229 ). Furthermore, higher levels of IGF-1 are associated with higher bone mineral density in adult obese individuals ( 230 ).…”
Section: Physiological Aspects Of Gh/igf-1 Axismentioning
confidence: 99%
“…These results are in line with the results of research conducted by Chalista et al (2017) that there is a relationship between IGF-1 levels and low bone mineral density (BMD). Likewise, the results of research conducted by Fornari et al (2017) concluded that there was a correlation between IGF-1 levels and lumbar and femoral BMD in obese subjects. Obesity is often associated with abnormalities in GH and IGF-1 secretion (Fornari et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…It is a primary mediator of the effects of growth hormone. Limited literature exists relating to IGF-1 and bone, however, in obese adults IGF-1 was reported to correlate with higher bone mineral density and the bone marker osteocalcin [29]. In another recent study, low serum IGF-1 was found to be a marker for frailty, lower BMD, and reduced handgrip [30], suggesting its generic utility as a marker of musculoskeletal health.…”
Section: Discussionmentioning
confidence: 99%